Prediction of logical interactions between Ribosomal Protein L22 with the factors of epstein barr virus genes using in silico strategy - Athma Hafeeza, binti Marzuki (Universiti Malaysia Sarawak (UNIMAS), 2015)
Epstein Barr virus (EBV) was first discovered in Burkitt-Lymphoma cells. It was later found in nasopharyngeal cancer (NPC) cells, which attracts the attention of many researchers. EBV genes produces some factors when the genes are expressed. The factors produced include basic tegument proteins, glycoproteins, capsid proteins, nuclear antigens as well as RNAs. Previous studies show that EBER 1, one of these factors somehow interact with ribosomal protein L22, which was found in the 60S large ribosomal subunit of the ribosomes. Its function remains unknown, but somehow its association with one of the factors from EBV genes was believed to be the cause of cancer. Thus, this study was conducted to perform the prediction of interaction between RPL22 with the factors of EBV genes using bioinformatics tools, and at which region of the proteins or RNAs do they interact. The research involves the analysis and aligning of multiple sequences for template selection, and the prediction of molecular models of the proteins and RNAs involved, besides the docking attempts of two models to find the possible interaction. Seven of the EBV factors were successfully generated and docked with RPL 22. Root mean square distance (RMSD) calculated between the docked proteins show strong interactions between RPL 22 and seven of the factors, which interaction may lead to arrested biological functions such as apoptosis, cell signaling and cell proliferation.